2017
DOI: 10.1016/j.juro.2017.04.079
|View full text |Cite
|
Sign up to set email alerts
|

The Nonpalpable Testis: A Narrative Review

Abstract: Purpose While the nonpalpable testis represents only a small portion of all cryptorchid testes, it remains a clinical challenge for pediatric urologists. Many controversies about the best evaluation and management exist. This narrative review serves as an update on what is known about the nonpalpable testis: etiology, pre-operative evaluation, the best surgical management, novel techniques, and ongoing controversies. Materials and Methods A Pubmed® and MEDLINE® search limited to January 2000 to January 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 112 publications
0
12
0
7
Order By: Relevance
“…Then laparoscopy/surgery can be postponed some months to identify and, if present, remove testicular remnants/nubbins in order to avoid leaving those absolutely extremely rare remnants/nubbins with left viable germ cells and only casuistic described malignant potential in situ [Thorup et al, 2011a;Shepard and Kraft, 2017].…”
Section: Neonatal Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…Then laparoscopy/surgery can be postponed some months to identify and, if present, remove testicular remnants/nubbins in order to avoid leaving those absolutely extremely rare remnants/nubbins with left viable germ cells and only casuistic described malignant potential in situ [Thorup et al, 2011a;Shepard and Kraft, 2017].…”
Section: Neonatal Periodmentioning
confidence: 99%
“…Other rarely performed alternative techniques, including among others staged orchidopexy with vessel preservation and auto-transplantation, may be used for selected cases. Especially, high bilateral intraabdominal cases with long distance between the testis and the internal inguinal annular ring and very sparse collateral blood supply in the gubernaculum and around the vas deferens are challenging [Shepard and Kraft, 2017]. Auto-augmentation may theoretically be the most viable option for such cases and was first described in 1976 by Silber and Kelly, and a laparoscopically assisted version was described in 2002 by Tackett et al This single-staged procedure has been shown to decrease the risk of testicular compromise by restoring blood flow immediately, as opposed to variations of Fowler Stephens orchidopexy [Kelly et al, 2010].…”
Section: Six Months To 1 Year Of Agementioning
confidence: 99%
See 1 more Smart Citation
“…While the routine use of ultrasound (US) by primary care physicians to diagnose cryptorchidism is common, there is no compelling evidence to support its use [20,32]. In a survey by Tasian et al, 67% of respondents ordered imaging as part of pre-surgical evaluation and 96% used US [21].…”
Section: Use Of Adjunctive Imaging Modalitiesmentioning
confidence: 99%
“…The success rate of laparoscopic single stage orchiopexy is reported to range from 87-97% and the 2-stage Fowler-Stephens orchiopexy demonstrates a success rate of 63-96%. The greatest risks following laparoscopic orchiopexy include varying degrees of testicular atrophy and secondary testicular ascent [2,20].…”
Section: Treatmentmentioning
confidence: 99%